A study of maternal near miss cases in tertiary health centre in north India - Kaur, Lovepreet; Mohi, Manjit Kaur; Kaur, Balwinder; Singh, Beant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal near miss is defined as woman who nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy. Methods: It was one-and-a-half-year prospective study from April 2016 to September 2017 conducted in the department of Obstetrics and Gynecology, Government Medical College, Patiala. The causes of maternal near miss based on WHO 2010 Near Miss criteria were studied. Results: In the present study out of total deliveries of 6166, there were 5461 live births and 123 maternal near miss cases which were included based on WHO 2010 maternal near miss approach. The maternal near miss incidence ratio (MNMR) in present study is 22.5. Literature reports the similar trends and MNMR varies between 15 to 40 per 1000 live births. Maternal near miss to mortality ratio is 1.89:1 in the present study. Conclusions: The most common direct cause for maternal near miss is hemorrhage. Severe preeclampsia is one of the easiest identifiable and avoidable factors for preventing maternal death. Studying near miss in detail allows us proper assessment of opportunities that were missed, analyzing the gaps and patient care related factors and helps to develop an audit system for maternal care.